Sistem Transmisi pada Mesin Pembersih Sepatu Safety Semi Otomatis - Muhammad Alfian; Hendi Lilih Wijayanto; Kadriadi Kadriadi; Muzadkir Jafar (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The transmission system is a system that functions to change the torque and speed (rotation) of the torsion engine and has a different speed to keep it moving, the transmission system usually uses gears and fulleys as a rotation successor. Safety shoes are very important protective equipment to prevent injury from falling objects. In addition, it is very important to keep safety shoes clean to avoid falling or slipping while working. In a previous study, namely the Design of a Safety Shoes Cleaner, it did not use a transmission system so that the rotation of the electric motor shaft which was transmitted to the cleaning brush experienced a very large resistance and frictional force. In this study, the transmission system used in the shoe cleaning machine is gear transmission and pulley transmission, the number of gears used is 2 which type of gear used is bevel gear while the number of pulleys used is 5. The purpose of this study was to modify the transmission system of the safety shoe cleaning machine so that it produces counterclockwise rotation on the brush shaft at the top of the machine. This research was carried out in the repair laboratory and workshop of the Morowali metal industry polytechnic from April to September 2022, the research method consisted of planning, designing and manufacturing processes, then testing was carried out so that it could be concluded that the transmission system was running well. By pairing two straight gears on the engine transmission system so as to produce opposite rotation on the upper brush shaft which is transmitted from the motor to the shaft through the gear transmission and fulley belt.